Advances in Imaging Multiple Sclerosis - Bischof, Antje; Caverzasi, Eduardo; Cordano, Christian; Hauser, Stephen L.; Henry, Roland G. (Seminars in Neurology, 2017)
Neuroimaging has emerged as a powerful technology that has enabled visualization of the impact of multiple sclerosis (MS) on the central nervous system in vivo with unprecedented precision. It has played a crucial role in disentangling the chronology of inflammation and neurodegeneration, developing and understanding mechanisms of novel therapeutics, and diagnosing and monitoring the disease in the clinical setting. However, challenges pertaining to the limited resolution, lack of specificity, inherent technological biases, and processing of increasingly big datasets have hindered comprehensive insights into the pathology underlying disability.Here, we review the advances in neuroimaging for MS that have moved the field forward in recent years by addressing the above-mentioned issues, thereby enhancing our knowledge of this yet enigmatic disease. We discuss complementary imaging technologies, including magnetic resonance imaging, positron emission tomography, and optical coherence tomography, the most recent tool in the MS imaging armamentarium that holds promise to act as a surrogate of pathological changes in the central nervous system in a more easily accessible way.
Keywords: multiple sclerosis; magnetic resonance imaging; positron emission tomography; optical coherence tomography; atrophy